Exploring the impact of three-dimensional patient satisfaction structure on adherence to medication and non-pharmaceutical treatment: a cross-sectional study among patients with hypertension in rural China - Meng Zhang; Wenqin Chen; Yanyun Xu; Jiyuan Fang; Yinzi Liu; Xiang Liu; Liyuan Song (BMC Primary Care)
Abstract Background Hypertension is a chronic disease that requires strict adherence to therapeutic recommendations. While some studies have shown an association between hypertensive patient satisfaction and treatment adherence, research on the relationship between multi-dimensional satisfaction and patient adherence to medication as well as non-pharmaceutical treatment remains limited. This study aimed to examine the association among multiple dimensions of patient satisfaction and adherence among patients with hypertension in rural China. Methods The research has a cross-sectional study design. A multi-stage, stratified random sampling approach was employed to survey a cohort of 2350 patients with hypertension in rural China. Patient satisfaction and adherence were measured using the instrument of European Task Force on Patient Evaluation of General Practice (EUROPEP) and the Treatment Adherence Scale for Hypertension Patients (TASHP). Multiple linear regression analysis was performed to identify factors influencing patient adherence, while structural equation modeling (SEM) was conducted to elucidate the relationships among various dimensions of patient satisfaction and adherence. Results Our findings indicate that patient satisfaction with clinical behavior was positively associated with medication adherence (β = 0.088, p < 0.05) and non-pharmaceutical treatment adherence (β = 0.152, p < 0.01). Patient satisfaction with continuity and cooperation also had a positive influence on medication adherence (β = 0.177, p < 0.01) and non-pharmaceutical treatment adherence (β = 0.134, p < 0.01). However, although patient satisfaction with the organization of care had a negative impact on medication adherence (β=-0.259, p < 0.01), it did not affect non-pharmaceutical treatment adherence. Further, patient adherence was associated by region, age, level of education, course of the disease, and self-reported health status. Conclusions Our study highlights the importance of understanding the differential effects of patient satisfaction on adherence in rural China. To improve the management of patients with hypertension in rural areas, primary care institutions should focus on enhancing their capacity, improving the level and capabilities of their chronic disease management team members, promoting effective doctor-patient communication, and providing personalized health education.